Reintroducing Autochthonous Minor Grapevine Varieties to Improve Wine Quality and Viticulture Sustainability in a Climate Change Scenario - Tommaso Frioni; Elia Romanini; Silvia Pagani; Filippo Del Zozzo; Milena Lambri; Alberto Vercesi; Matteo Gatti; Stefano Poni; Mario Gabrielli (Australian Journal of Grape and Wine Research)
One of the major challenges that global warming poses to viticulture is the maintenance of adequate acidity at maturity in white grapes for sparkling winemaking. This issue arises from three main occurrences: (i) with higher temperatures, degradation of malic acid is significantly enhanced; (ii) with a general advancement in grapevine phenology, grape maturity may occur under suboptimal climatic conditions; and (iii) harvesting grapes at “traditional” dates results in overripe fruits for sparkling destinations. In this biennial work, we compared the fruit and must composition of a local, widely grown white grape variety in the Colli Piacentini area (cv. Ortrugo, ORT) with those of a minor autochthonous variety, namely, Barbesino (BRB). Furthermore, we compared the composition, aromatic, and sensory profiles of wines obtained from ORT and BRB grapes picked on the same date and, in addition, of a second Barbesino wine from late harvest (BRB-LH). ORT and BRB had a similar sugar accumulation dynamic, whereas BRB exhibited a delayed loss of titratable acidity. In more details, BRB had lower malic acid degradation rates when malate concentration was <9 g/L. As a result, with comparable yield and total soluble solid content (TSS) (∼20°Brix), BRB had a higher berry titratable acidity and malic acid concentration at harvest than ORT. BRB wines showed the highest titratable acidity (TA), while ORT had the lowest TA and a higher pH, and as expected, BRB-LH had the highest pH and a lower TA than BRB although still higher than those of ORT wine. The aroma profiles of wines were mainly characterized by fermentative aromas, including esters, fatty acids, higher alcohols, and C6 compounds, and BRB-LH wines showed the highest concentration of higher alcohols, while the fermentative esters were higher in ORT wines. Panelists considered BRB significantly fresher and with bigger aroma intensity than ORT, confirming that the higher acidity detected in BRB musts is well preserved in final wines. Our work demonstrates that local minor varieties can be reconsidered in light of the new climate change-related issues impairing viticulture sustainability today. In particular, currently neglected cultivars could help preserve must acidity as compared to traditional varieties having early ripening, maintaining the links with terroir and local traditions at the same time.